A low-cost neurostimulator with accurate pulsed-current control - De Lima, J. A.; Cordeiro, A. S. (Institute of Electrical and Electronics Engineers (IEEE), 2002)
A constant-current stimulator for high-impedance loads using only low-cost standard high-voltage components Is presented. A voltage-regulator powers an oscillator built across the primary of a step-up transformer whose secondary supplies, after rectification, the high voltage to a switched current-mirror in the driving stage. Adjusting the regulated voltage controls the pulsed-current intensity. A prototype produces stimulus of amplitude and pulsewidth within 0 less than or equal to I-skin less than or equal to 20 mA and 50 mus less than or equal to T-pulse less than or equal to 1 ms, respectively. Pulse-repetition spans from 1 Hz to 10 Hz. Worst case ripple is 3.7% at I-skin = 1 mA. Overall consumption is 5.6 W at I-skin = 20 mA.
Keywords: current source; current stimulator; electrocutaneous stimulation; high voltage